Anti-demineralization effect of desensitizer containing copolymer and sodium fluoride on root dentin – a transverse microradiographic study. Issue 1 (2nd December 2019) - Kawamura, Kazuaki; Kunimatsu, Yuichi; Nakano, Takafumi; Hasegawa, Haruhiko; Arakawa, Hirohisa; Mukai, Yoshiharu
Abstract: Objective: To evaluate anti-demineralization effects of dentin desensitizer containing sodium fluoride and methacrylate-co-p-styrene sulfonic acid (MS polymer) on root dentin using transverse microradiography (TMR). Material and methods: Twenty-four dentin specimens were divided into four groups: MSO (no fluoride), MSF (3000 ppm F), FJL (9000 ppm F), and Control. In MSO and MSF, each desensitizer was rubbed into the dentin surfaces for 10 s then left for 20 s. In FJL, paste containing 9000 ppm F was applied onto the surface for 30 s. All specimens, including the Controls, were rinsed with deionized water, dried and an area of their surface exposed to pH 5.0 acidic solution, refreshed every 24 h, for 4 days. Sections 300-µm-thick were assessed by TMR. Mineral profiles and integrated mineral loss (IML) of lesions were analyzed by dedicated software. IML was analyzed with one-way ANOVA and Tukey's test. Results: MSF and FJL specimens showed high mineral volume % at the surface and in lesions, and significantly lower IML than the other groups ( p < .05). Conclusion: Dentin desensitizer containing 3000 ppm fluoride and MS polymer has the same anti-demineralization effect as does a fluoride paste containing 9000 ppm F.